ANALISIS USAHATANI DAN PENGELUARAN RUMAH TANGGA PETANI PADI SAWAH LEBAK DI DESA SUNGAI DUA KABUPATEN BANYUASIN - Endang Lastinawati; Chuzaimah Chuzaimah (Journal of Integrated Agribusiness, 2023)
Rice is a staple food commodity that is cultivated by the majority of farmers, both to meet household food needs, as well as to be sold and exchanged for other consumption needs. This study aimed to analyze the income of rice farming and the household expenditure of rice farmers. The research was conducted in Sungai Dua Village, Banyuasin Regency, South Sumatra Province. The location of the study was determined purposively because it has a distinctive land characteristic, namely in the form of a lowland swamp. The research sample consisted of 30 rice farmers who were taken at simple random sampling. The data was processed using a mathematical formula of farm income and household consumption expenditure, which is then explained in a quantitative descriptive manner. The results showed that the income of rice farming in Sungai Dua Village was IDR. 19,125,908.00 per growing season. Expenditures for rice production and household consumption were IDR. 5,935,652.00 and IDR. 6,004,888.89 per growing season, respectively. The income from rice farming in Sungai Dua Village is not sufficient to cover the needs of rice farmers for a year, considering that the intensity of rice cultivation in Sungai Dua Village is only once a year. Therefore, the government needs to provide solutions through various policies and programs that can help farmers increase their income and improve their welfare without having to leave their rice farming.